Preferences of newly qualified healthcare professionals for working with people with dementia: a qualitative study. (13th November 2021) - Hebditch, Molly; Banerjee, Sube; Wright, Juliet; Daley, Stephanie
Abstract: Background: there is little research on preferences in students and newly qualified healthcare professionals for working with people with dementia. Understanding the development of these preferences can help inform strategies to increase workforce capacity in response to current suboptimal dementia care and the increasing numbers of people with dementia. Objective: to explore the factors that influence career preferences in relation to working with people with dementia. Specifically, to understand how these factors relate to early career doctors' and nurses' preferences and how they influence decisions and perspectives on their careers. Methods: qualitative in-depth interviews were conducted with 27 newly qualified doctors and nurses within 2 years of graduation. This included a subset of participants that had taken part in a dementia educational intervention during their undergraduate training. Transcripts were analysed using grounded theory methods. Results: the results present six main categories representing complex interlinked factors influencing preferences for working with people with dementia as well as exploring the definition of a career working with people with dementia. The factors include the importance of making a difference; seeing dementia care as a different type of care; its perceived alignment with personal characteristics; perceptions of people with dementia; care environments and career characteristics. Discussion: this is the first study to explore the factors influencing preferences for working with people with dementia in newly qualified healthcare professionals. It provides useful data to inform workforce planning, and curriculum and practice development to stimulate interest and drive improved quality of care.